Comparative Study of the Regulation and Planning of National Capital Authority-Owned Enterprises in Realizing Sustainable Development of the Nusantara's Capital City - Sadiawati, Diani; Dirkareshza, Rianda; Fauzan, Muhammad (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
After the stipulation of Presidential Decree no. 62 of 2022 concerning the Nusantara Capital Authority, the Authority can have power over business entities which is characterized by share control and ownership of shares of a business entity so that it becomes the domain of the IKN Authority in its management. However, in reality, adequate regulations to accommodate the formation and planning of the Authority-Owned Business Entity itself are not not yet in place. This research aims to find out how business entities owned by the state capital are regulated and planned in a comparative perspective and what the ideal concept of regulation and planning of authority owned business entities is in realizing sustainable development of the Nusantara Capital City. The research used normative juridical with a statutory approach, comparative approach and conceptual approach. The research results show that the concepts of the three countries are different. The concept from Australia requires the formation of a state-owned enterprise through the law of its capital region, namely the Territorial State-owned Corporation Act 1990. Meanwhile, India uses a registration mechanism by injecting funds from the government to mark it as a government-owned company according to its level in accordance with the provisions of the Company Law of India, 2013. Then China acknowledged the existence of controlling and non-controlling shares in government control as regulated in the Law of State-owned Assets Enterprise 2018 Revision. In this case, Indonesia can adopt it by establishing an authority-owned business entity using regulations from the head of the authority that are regulatory and based on sustainable development. In this way, the next generation can experience the development results of the authority's business entities.